Advancing giga-strength and high-modulus aluminum matrix composites via nitrogen-induced self-forming process - Kanhu C. Nayak; Se-Hoon Kim; Jin-Won Lee; Donghyun Bae; Jae-Pyong Ahn; Kon-Bae Lee; Hyun-Joo Choi (Journal of Materials Research and Technology)
Giga-strength Al/SiC composites with exceptional strength (>1 GPa) and stiffness (>200 GPa), yet low density (<3.0 g/cm3), are produced through a simple yet transformative process that utilizes nitrogen's critical influence on the matrix-reinforcement interface, known as Nitrogen-Induced Self-Forming Aluminum Composites (NISFAC). The Al matrix, reinforced with 20–50 vol% microsized SiC particles, exhibited significant enhancements of mechanical properties, with a 471.93 % increase in compressive strength and a 189.33 % improvement in Young's modulus compared to monolithic aluminum. These improvements are attributed to the formation of aluminum nitride (AlN) and aluminum oxynitride (Al(O)N), which originate on the Al powder surface and integrate into the matrix and Al–SiC interface during the nitrogen-induced self-sintering process. Detailed microstructural analysis revealed the critical role of these phases in load transfer from the matrix to the reinforcement. Mechanistic insights and novel predictive models further validated the contributions of reinforcements to the yield strength and Young's modulus. The Al/50 %SiC composite achieved compressive strength over 1 GPa and Young's modulus over 200 GPa, highlighting its potential for advanced structural applications.